2018
DOI: 10.5004/dwt.2018.22375
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of ground and groundwater factors affecting NMR probe

Abstract: With the development of science and technology, nuclear magnetic resonance (NMR) phenomenon has been studied. It has already entered the stage of application and development by theoretical research and test. In addition, it has also been widely used in geoscience (proton magnetometer, NMR spectrometer, core testing instrument and NMR logging). On the basis of this, the NMR technique is proposed to detect the numerical simulation of groundwater. The simulation model of layered earth aquifer is established. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Tender and over-mature coconut water at 4 mL/100 g can effectively inhibit plantar edema in rats induced by acetic acid, and the inhibition rates were 35.13% and 25.94% after 2 h treatment, respectively [4]. And in emergency situations, coconut water can also be used as a substitute for physiological saline for short-term intravenous injection because of its high content of potassium, sodium, magnesium, and other mineral elements and an osmotic pressure like that of human blood [6,7]. Therefore, its natural, nutritious, and healthy properties make coconut water more and more popular with consumers, and its market consumption scale is also increasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tender and over-mature coconut water at 4 mL/100 g can effectively inhibit plantar edema in rats induced by acetic acid, and the inhibition rates were 35.13% and 25.94% after 2 h treatment, respectively [4]. And in emergency situations, coconut water can also be used as a substitute for physiological saline for short-term intravenous injection because of its high content of potassium, sodium, magnesium, and other mineral elements and an osmotic pressure like that of human blood [6,7]. Therefore, its natural, nutritious, and healthy properties make coconut water more and more popular with consumers, and its market consumption scale is also increasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…4 (breeding from Aromatic Green Dwarf (AROD) in Thailand) and Wenye 78F1 (cross-breeding from the mother of MYD and the father of Hainan Tall), and the cultivation proportion of the Hainan Tall variety is also more than 80% [9]. In general, the growth, nutritional composition, and volatile flavor of coconut water are influenced by various factors such as maturity, variety, and cultivation conditions [7][8][9][10][11][12][13][14][15][16]. For example, Kumar et al (2021) found that maturity was a key factor affecting the physicochemical properties, as well as the nutritional (free amino acid, protein, sugar, and ascorbic acid) and metabolic components of coconut water from COD and MYD [8].…”
Section: Introductionmentioning
confidence: 99%